Bereken de getalwaarde
- \(4a-4b\text{ [met a = -2 en b = -4]}\)
- \(5a^2+6b\text{ [met a = 6 en b = 6]}\)
- \(3a+5b\text{ [met a = 4 en b = 3]}\)
- \(3a+7b\text{ [met a = 1 en b = -5]}\)
- \(4ab+3b-2\text{ [met a = 1 en b = 2]}\)
- \(ab+b-14\text{ [met a = -2 en b = 1]}\)
- \(3a^2+6b\text{ [met a = -5 en b = -3]}\)
- \(7a-4b\text{ [met a = 1 en b = -5]}\)
- \(4a^2+4b\text{ [met a = -3 en b = -1]}\)
- \(4a^2-4b\text{ [met a = 5 en b = -3]}\)
- \(3a^2-4b\text{ [met a = -3 en b = 4]}\)
- \(a^2+3b\text{ [met a = -1 en b = 5]}\)
Bereken de getalwaarde
Verbetersleutel
- \(\begin{align} 4a-4b&=4.a-4.b \text{ [met a = -2 en b = -4]}\\&=4.(-2)-4.(-4)\\&=8\\ \end{align}\)
- \(\begin{align} 5a^2+6b&=5.a^2+6.b \text{ [met a = 6 en b = 6]}\\&=5.6^2+6.6\\&=216\\ \end{align}\)
- \(\begin{align} 3a+5b&=3.a+5.b \text{ [met a = 4 en b = 3]}\\&=3.4+5.3\\&=27\\ \end{align}\)
- \(\begin{align} 3a+7b&=3.a+7.b \text{ [met a = 1 en b = -5]}\\&=3.1+7.(-5)\\&=-32\\ \end{align}\)
- \(\begin{align} 4ab+3b-2&=4.a.b+3.b-2 \text{ [met a = 1 en b = 2]}\\&=4.1.2+3.2-2\\&=12\\ \end{align}\)
- \(\begin{align} ab+b-14&=1.a.b+1.b-14 \text{ [met a = -2 en b = 1]}\\&=1.(-2).1+1.1-14\\&=-15\\ \end{align}\)
- \(\begin{align} 3a^2+6b&=3.a^2+6.b \text{ [met a = -5 en b = -3]}\\&=3.(-5)^2+6.(-3)\\&=57\\ \end{align}\)
- \(\begin{align} 7a-4b&=7.a-4.b \text{ [met a = 1 en b = -5]}\\&=7.1-4.(-5)\\&=27\\ \end{align}\)
- \(\begin{align} 4a^2+4b&=4.a^2+4.b \text{ [met a = -3 en b = -1]}\\&=4.(-3)^2+4.(-1)\\&=32\\ \end{align}\)
- \(\begin{align} 4a^2-4b&=4.a^2-4.b \text{ [met a = 5 en b = -3]}\\&=4.5^2-4.(-3)\\&=112\\ \end{align}\)
- \(\begin{align} 3a^2-4b&=3.a^2-4.b \text{ [met a = -3 en b = 4]}\\&=3.(-3)^2-4.4\\&=11\\ \end{align}\)
- \(\begin{align} a^2+3b&=1.a^2+3.b \text{ [met a = -1 en b = 5]}\\&=1.(-1)^2+3.5\\&=16\\ \end{align}\)